2021
DOI: 10.1111/1440-1703.12204
|View full text |Cite
|
Sign up to set email alerts
|

Bilberry seed production explains spatiotemporal synchronicity in bank vole population fluctuations in Norway

Abstract: Population fluctuations of small rodents are often synchronized over larger areas (>100 km) than what could be explained by dispersal, suggesting that the synchronizing factor is weather‐related and possibly mediated through changes in food quality. Because bank vole (Myodes glareolus) populations usually peak 1 year after peaks in reproduction of the staple winter food plant bilberry (Vaccinium myrtillus), we tested for a possible link between food and spatial synchrony by comparing the synchrony in bank vole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…One possible reason may be the return of more regular rodent cycles with larger peaks from ca. 2005–2010 after a period of dampened cycles starting around 1990 (Brommer et al 2010 ; Wegge and Rolstad 2018 ; Selås et al 2021 ; Sonerud 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible reason may be the return of more regular rodent cycles with larger peaks from ca. 2005–2010 after a period of dampened cycles starting around 1990 (Brommer et al 2010 ; Wegge and Rolstad 2018 ; Selås et al 2021 ; Sonerud 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…If conditions are predictably negatively correlated between source and destination areas, irruptive birds may be drawn to areas with better conditions than where they originate. Synchrony in masting years of trees and peak rodent years may range over hundreds or even thousands of kilometres (Koenig and Knops 1998 ; Sundell et al 2004 ; Gallego Zamorano et al 2018 ; Fay et al 2020 ; Selås et al 2021 ). Irruptive birds may therefore need to travel long distances to find areas with higher food availability than where they came from, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…V . myrtillus is a keystone species in boreal and low‐alpine areas as it is highly abundant and both the fleshy fruits and vegetative parts provide an important food source for animals (Hegland et al, 2010 and references therein, Selås et al, 2021 ). This early‐flowering, deciduous, clonal dwarf‐shrub is partly selfing, and its main pollinators are bumblebees, bees, and wasps (Ritchie, 1956 ), of which bumblebees are dominant in alpine habitats.…”
Section: Methodsmentioning
confidence: 99%
“…After correcting for ramet coverage, berry abundance was indexed as numbers per 1 m 2 of bilberry plants. We also had access to bilberry fruit indices in the study area for the whole period of 41 years, based on newspaper records (Selås et al, 2021). Parallel analyses for the final 17 years, using either our field measurements or the newspaper index, gave very similar results (Appendix S1: Chick food)—we therefore used the latter here.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, while the prediction of the Plant Stress sub-hypothesis that previous year's bilberry production should be related to breeding success was clearly verified, path analysis showed that this was due in part to an indirect relationship via voles. It may have been that high bilberry fruit crops increased the overwinter survival of bank voles (Selås et al, 2021), which subsist mainly on bilberry shoots during winter (Hansson, 1983), thereby buffering predation on nests and chicks via APH.…”
Section: Confounding Effects and Biological Causationmentioning
confidence: 99%